Consensus on Severity for Ocular Emergency: The BAsic SEverity Score for Common OculaR Emergencies [BaSe SCOrE] - Jean-Louis Bourges; Isabelle Boutron; Dominique Monnet; Antoine P. Brézin (Journal of Ophthalmology)
Purpose. To weigh ocular emergency events according to their severity. Methods. A group of ophthalmologists and researchers rated the severity of 86 common ocular emergencies using a Delphi consensus method. The ratings were attributed on a 7-point scale throughout a first-round survey. Then, the experts were provided with the median and quartiles of the ratings of each item to reevaluate the severity levels being aware of the group’s first-round responses. The final severity rating for each item corresponded to the median rating provided by the last Delphi round. Results. We invited 398 experts, and 80 (20%) of them, from 18 different countries, agreed to participate. A consensus was reached in the second round, completed by 24 experts (43%). The severity ranged from subconjunctival hemorrhages (median = 1, Q1 = 0; Q3 = 1) to penetrating eye injuries collapsing the eyeball with intraocular foreign body or panophthalmitis with infection following surgery (median = 5, Q1 = 5; Q3 = 6). The ratings did not differ according to the practice of the experts. Conclusion. These ratings could be used to assess the severity of ocular emergency events, to serve in composite algorithms for emergency triage and standardizing research in ocular emergencies.